Vertically oriented mesoporous silica film modified fluorine-doped tin oxide electrode for enhanced electrochemiluminescence detection of lidocaine in serum. Issue 55 (26th October 2021) - Liang, Renchuan; Jiang, Jinghang; Zheng, Yanyan; Sailjoi, Ajabkhan; Chen, Jie; Liu, Jiyang; Li, Hongxue
Abstract : Sensitive detection of lidocaine in serum is realized using enhanced electrochemiluminescence based on a vertically oriented mesoporous silica film modified fluorine-doped tin oxide electrode. Abstract : Owing to a nanochannel-based enrichment effect and anti-fouling ability, highly ordered and vertically oriented mesoporous silica thin film (VMSF) modified electrodes have demonstrated their great potential in direct and highly sensitive analysis of complex samples. In this work, a VMSF modified fluorine-doped tin oxide (FTO) electrode (VMSF/FTO) is fabricated for enhanced electrochemiluminescence (ECL) analysis of lidocaine in serum. VMSF with good integrity and mechanical stability can be rapidly and conveniently grown on FTO in a few seconds at room temperature using an electrochemically assisted self-assembly (EASA) method. Due to the strong electrostatic attraction between the cationic ECL probe and negatively charged nanochannel, the VMSF/FTO electrode shows significant enrichment of tris(2, 2-bipyridine) ruthenium(ii ) (Ru(bpy)3 2+ ), leading to ∼10 times enhancement of its ECL signal in comparison to the bare FTO electrode. Lidocaine, an anesthetic and antiarrhythmic drug, can act as the co-reactant of Ru(bpy)3 2+ and promote its ECL signal. Sensitive ECL detection of lidocaine is achieved by the sensor in a wide linear range from 10 nM to 50 μM with a low limit-of-detection (LOD) of 8 nM. Combined with the antifouling ability of VMSF, the VMSF/FTO electrode also realizes the accurate and rapid analysis of lidocaine in real serum samples.